Sequence requirements for stable binding and function of Rep68 on the adeno-associated virus type 2 inverted terminal repeats. - Chiorini, J A (1994)
Replication of the palindromic inverted terminal repeats (ITRs) of adeno-associated virus type 2 requires several functions of the viral nonstructural Rep proteins. These include binding to the ITR, nicking of the double-stranded replication intermediate at the terminal resolution site (trs), and then strand displacement and synthesis from the nick. This report demonstrates the ability of both recombinant fusion maltose-binding protein (MBP)-Rep68 delta produced in Escherichia coli and wild-type (wt) Rep68 to bind to a linear truncated form of the ITR, delta 57 ITR, with similar affinity as to the wt hairpin ITR. A dissociation constant for MBP-Rep68 delta of approximately 8 x 10(-10) M was determined for the wt ITR and delta 57 ITR probes. Truncation of delta 57 ITR to generate delta 28 ITR, which retains the GCTC repeat motif but not the trs, bound at least 10 times less efficiently than delta 57 ITR. Extension of delta 28 ITR with nonspecific sequence restored the ability of MBP-Rep68 delta to bind to delta 28 ITR. Thus, high-affinity binding would appear to require stabilization by flanking sequence as well as the intact GCTC repeat motif. Cleavage of the delta 57 ITR probe with DdeI, which truncates the flanking sequence and was previously shown to inhibit binding by Rep68, also inhibited the binding of MBP-Rep68 delta. The requirements for stable binding were further defined with a series of oligonucleotide probes which spanned the region protected by MBP-Rep78 in DNase I footprinting. The binding activity of either MBP-Rep68 delta or wt Rep68 to hairpin ITR or delta 57 ITR was indistinguishable. However, the binding activity of MBP-Rep68 delta to DNA does not appear to correlate with trs endonuclease activity. The nicking and covalent linkage of MBP-Rep68 delta to the nonhairpin delta 57 ITR was approximately 100-fold less efficient than its linkage to a hairpin-containing ITR. Therefore, although the hairpin portion of the ITR does not appear to play a role in recognition and stabilization of MBP-Rep68 delta binding, its presence does affect the trs cleavage activity of the protein.